PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS VIII - listri damayanti (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
In learning Indonesian, which is listed in the 2013 curriculum, there are texts that must be studied, including explanatory text. In learning, students are expected to be able to participate actively and critically in every lesson they participate in, students are expected to develop their own knowledge, and students also at the end of their learning that have been studied must be able to produce products in the form of explanatory text. This study aims to see the effect of the Problem Based Learning method on students' writing ability through explanatory text, because in the learning process students still have difficulty producing a product or their writing. This study used an experimental method, from the results of the research that had been carried out, the average value of the initial test score was 57.5 and for the final test it was obtained 75.5 and finally there was a difference in this study so that according to statistical calculations it was also obtained tcount = 4.38 > ttable = 2.00, which means that the final test is greater than the initial test. And based on the results of hypothesis testing, it can be obtained with a sig: 0.000 value smaller than 0.05, then the alternative hypothesis is accepted and the null hypothesis is rejected. Thus the Problem Based Learning method greatly influences the learning process, because students can think critically in solving problems and this method is very effective in the learning process of writing explanatory text.